SUFFIX –IS AND –IK AND ITS PROBLEMATICS IN INDONESIAN LANGUAGE - Umi Kulsum (Balai Bahasa Jawa Barat, 2015)
ALTHOUGH suffix –is and –ik are not genuinely Indonesian suffixes they are quiteproductive suffixes. They are very interesting to observe since they vary in forms,functions, and meanings compared to other suffixes. Another problem is thatpeople use both suffixes as if they were interchangeable while the media seem touse them arbitrarily. It needs to be noticed and taken care of especially onderivatives containing either of both suffixes with the same meaning. Anotherproblem to solve is the entries containing the suffixes in Kamus Besar BahasaIndonesia. This writing aims to describe suffixes –is and –ik within the derivativesaccording to their forms, functions, meanings, formulas, and their problematicusing descriptive method and referential equivalence in analyzing the data. Datawere taken from mass media such as Kompas, Pikiran Rakyat, Koran Tempo,and tabloid Nakita. The conclusions were (1) there were six variations of rootverbs that could be followed by the suffix –is and –ik, (2) suffix –is had morevariations in terms of function and meaning than that of suffix –ik. Suffix –is hadfour functions of noun determiner and two functions as adjective determiner,meanwhile suffix –ik only had two functions of meaning determiner; (3) therewere three derivation formulas involving suffix –is and –ik; (4) the problematicconcerning suffix –is and –ik can be classified into four categories.